The E-Research Project: Developing an IMM Resource for Supporting Communities of Learners Through CSCL - Winter, Christine (Proceedings of the International Conference on Networked Learning, 2004)
In this paper I discuss learning issues arising from the design and development of an IMM resource, the E Research CDRom, for teaching postgraduate students about educational research methodologies in networked collaborative learning environments. The main features of the CDRom are described and the policy and practice context for its production given. The main part of the paper focuses on eight learning and design issues that arose from both the literature and the practical experience of developing the CDRom. In the conclusion, I briefly describe the limitations of the resource and possible directions for future research.